Support for children with disabilities and special educational needs - Eduin Latimer; Luke Sibieta; Darcey Snape (Institute for Fiscal Studies (IFS), 2025)
This work contains statistical data from the Office for National Statistics (ONS), which are Crown Copyright. The use of the ONS statistical data in this work does not imply the endorsement of the ONS in relation to the interpretation or analysis of the statistical data. This work uses research datasets which may not exactly reproduce National Statistics aggregates. The work was carried out in the Secure Research Service, part of the Office for National Statistics.
Keywords: 330; Education and skills; Employment and income; Government finances and spending; Health and social care; Poverty; inequality and social mobility; Taxes and benefits; Benefits; Disability; Early childhood development; Educationm; Employment; Gography; Government spending; Health; Inequality; Schools; Trends; Working age benefits; SEND